A study protocol for a multicentre, prospective, before-and-after trial evaluating the feasibility of implementing targeted SEDation after initiation of mechanical ventilation in the emergency department (The ED-SED Pilot Trial). Issue 12 (16th December 2020) - Fuller, Brian M; Roberts, Brian W; Mohr, Nicholas M; Pappal, Ryan D; Stephens, Robert J; Yan, Yan; Carpenter, Chris; Kollef, Marin H; Avidan, Michael Simon
Abstract : Introduction: Sedation is a cornerstone therapy in the management of patients receiving mechanical ventilation and is highly influential on outcome. Early sedation depth appears especially influential, as early deep sedation is associated with worse outcome when compared with light sedation. Our research group has shown that patients receiving mechanical ventilation in the emergency department (ED) are exposed to deep sedation commonly, and ED sedation depth is impactful on intensive care unit (ICU) care and clinical outcomes. While extensive investigation has occurred for patients in the ICU, comparatively little data exist from the ED. Given the influence that ED sedation seems to carry, as well as a lack of ED-based sedation trials, there is significant rationale to investigate ED-based sedation as a means to improve outcome. Methods and analysis: This is a multicentre (n=3) prospective, before-and-after pilot trial examining the feasibility of implementing targeted sedation in the immediate postintubation period in the ED. A cohort of 344 patients receiving mechanical ventilation in ED will be included. Feasibility outcomes include: (1) participant recruitment; (2) proportion of Richmond Agitation-Sedation Scale (RASS) scores in the deep sedation range; (3) reliability (agreement) of RASS measurements performed by bedside ED nurses; and (4) adverse events. The proportion of deep sedation measurements before and after the intervention will be compared using the χ 2 test. Logistic regression will be used to compare before-and-after differences, adjusting for potential confounders. The inter-rater correlation coefficient will be used to assess paired observations between a study team member and bedside ED nurses, and to describe reliability of RASS measurements. Ethics and dissemination: The Human Research Protection Office at Washington University in St. Louis School of Medicine has approved the study. The publication of peer-reviewed manuscripts and the presentation of abstracts at scientific meetings will be used to disseminate the work. Registration: ClinicalTrials.gov identifier NCT04410783; Pre-results .